Design and Application of the Hazard Assessment For Center Disaster Control Of Operations East Java Web Based - Dhesky Aris Mas Darwanto; dewiyani sunarto; ignatius adrian mastan (Jurnal Sistem Informasi Universitas Dinamika, 2015)
One task of Disaster Management Operation Control Center (Pusdalops-PB) is providing support for pre-disaster activities with the aim of anticipating the danger by collecting, processing and presenting data and disaster information. One of these activities is to assess the danger as the building blocks of contingency plans. However, there are problems such as difficulty in processing hazard assessment due to the lack of precise parameters.To overcome the problems faced, then Pusdalops PB need to create a web-based system that can assess the danger of the disaster in East Java. This system can be accessed by the informant through the medium of the web and SMS by sending the information and parameter values of the disaster. Information and values will be used as input parameters in the system do a hazard assessment.With this application can help the Pusdalops PB in assessing the danger of the disaster in East Java. Hazard assessment can be seen in a daily report that shows the value of the dangers of disasters. Informants can transmit disaster information and parameter values into the system to do a hazard assessment. This application can help BPBDs in the area in knowing the development of hazard assessment of the disaster.